2003
DOI: 10.1902/jop.2003.74.11.1634
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Herpesviruses in Patients with Aggressive Periodontitis

Abstract: These findings indicate that subgingival presence of EBV-1 HCMV is strongly associated with aggressive periodontitis, and coinfection with HCMV and EBV-1 appears to be particularly deleterious to periodontal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
6
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 42 publications
3
50
6
2
Order By: Relevance
“…In other research, it has been associated with aggressive and chronic periodontitis (Bilichodmath et al, 2009;Botero et al, 2007;Contreras et al, 2000;Ling et al, 2004, Yapar et al, 2003Saygun et al, 2004). We found that 8% of the individuals in our study from northeastern Mexico suffering from chronic periodontitis had HSV-1 present in the periodontal pockets.…”
Section: Discussionsupporting
confidence: 52%
“…In other research, it has been associated with aggressive and chronic periodontitis (Bilichodmath et al, 2009;Botero et al, 2007;Contreras et al, 2000;Ling et al, 2004, Yapar et al, 2003Saygun et al, 2004). We found that 8% of the individuals in our study from northeastern Mexico suffering from chronic periodontitis had HSV-1 present in the periodontal pockets.…”
Section: Discussionsupporting
confidence: 52%
“…This has led many investigators to look for a possible viral cause in the development of aggressive periodontitis. [7] Since the mid1990s viruses have emerged as putative pathogens in aggressive periodontitis, in particular Human cytomegalovirus (HCMV), Epstein-Barr virus (EBV) and Herpes simplex virus-1 (HSV-1). Herpesviruses seem to be the most important DNA viruses in oral pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In the immuno deficient, B cell clones may replicate unchecked, resulting in lymphomas (Yapar et al, 2003).…”
Section: Pathogenesis (Winkler Et Al 1988; Yapar Et Al 2003)mentioning
confidence: 99%